Favored isolation and rapid identification of Xanthophyllomyces dendrorhous (Phaffia rhodozyma) from environmental samples - Tognetti, Celia (2013)
Xanthophyllomyces dendrorhous (Phaffia rhodozyma) yeasts are biotechnologically exploited as a natural source of astaxanthin for aquaculture. Based on results of recent studies, it has become clear that this species possesses a greater genetic variability generating the necessity to uncover it and assess its potential for the astaxanthin industry. However, difficulties for the isolation of the X. dendrorhous hinder extensive environmental surveys which need to be carried out to better understand the habitat, distribution and genetic diversity of this species. We extensively searched for distinctive physiological traits of X. dendrorhours by testing phenotypic properties simultaneously with a panel of common sympatric fungi. As a result we obtained a new and innovative strategy for improving X. dendrorhous recovery rate and identification from environmental samples. This strategy involved the use of trehalose-based media, and a rapid X. dendrorhous identification method based on the simultaneous spectrophotometric detection of astaxanthin and UV-absorbing compounds (mycosporines). The proposed procedures proved effective in field trials conducted in natural environments of Patagonia (Argentina) and thus represent an important tool for the discovery of new astaxanthin-producing strains of X. dendrorhous useful for the aquaculture industry.